Application of high-pressure homogenization (HPH) to modify functional, structural and rheological properties of lentil (Lens culinaris) proteins - Sarıcaoğlu, Furkan Türker (Elsevier, 2020)
The ability of high-pressure homogenization (HPH) to modify the functional, structural and rheological properties of lentil protein isolate (LPI) suspensions were investigated. Protein patterns remained unchanged with HPH treatment. Particle size significantly decreased up to 100 MPa treatment and size distribution was mono-modal after 50 MPa. Microstructural images revealed that increasing pressure from 50 to 150 MPa caused further unfolding of protein particles, which well supported to water solubility, emulsifying, foaming and particle size results. LPI suspensions had shear thinning behavior and results were well fitted to Ostwald de-Waele model (R-2 >= 0.989). Apparent viscosity and homogenization pressure were modeled with exponential and sigmoidal functions (R-2 >= 0.983). However, weak gel-like structure was observed from all samples due to G' > G", and higher homogenization pressures than 50 MPa caused more pronounced gelation after 51.78 degrees C. These results stated that HPH treatment has a good potential to modify the functional, structural and rheological properties of LPI suspensions. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: High-pressure homogenization; Lentil protein isolate; Rheology